Activity of isolated specific bacteriophage in treatment of chronic osteomyelitis induced by multiple drug resistance Pseudomonas aeruginosa in Rabbits - Sarhan, Sarhan Rashid (The Iraqi Journal of Veterinary Medicine, 2018)
This study was conducted to find out the possibility of using the Pseudomonas aeruginosa specific-bacteriophage as an alternative to antibiotics in treatment of chronic osteomyelitis in rabbits by injection of Pseudomonas aeruginosa suspension in tibia. The current study included an isolation of bacteriophage from sewage water by using agar overlay method and also an isolation of the bacteria from patients suffering from post-traumatic bone infection. The second experiment was in-vivo evaluation of phage activity in treatment of chronic osteomyelitis in rabbits. All animals of infected groups with Pseudomonas aeruginosa before treatment exhibited histopathological changes after 35 days of infection, the infected groups showed chronic osteomyelitis represented by sever chronic inflammatory cells infiltrates mainly lymphocytes, and macrophages and hemorrhage between bone trabeculae, also some sections showed extensive fibrosis in the marrow spaces. The treated group with P. aeruginosa specific – bacteriophage (1.5 ×107) PFU/ml for 10 days showed early repair elucidated by presence whorls of chondrocytes, and also the presence of multiple osteoblasts indicated bone formations. Also the presence of extensive fibrosis in the marrow space with present of osteoblasts indicated bone formations and repair.